Achieving selves: From psychohistory to narratology in the analysis of entrepreneur life-writing. Issue 3 (11th October 2019) - Todres, Mathew; Reveley, James
Abstract : Purpose: Arguably, how psychohistorians treat entrepreneur life-writing interiorizes the autobiographer's self, thereby limiting the extent to which self can be accessed by researchers. By advocating a different approach, based on socio-narratology, this paper provides insight into how entrepreneurs in both the distant and recent past construct narrative identities – the textual corollary of "storied selves" – within their autobiographies. Design/methodology/approach: The object of analysis is the failed entrepreneur autobiography, straddling two sub-genres – "projective" and "confessional" – which both serve to rehabilitate the author. Findings: Narratological analysis of Nick Leeson's Rogue Trader autobiography reveals how the author deftly draws upon the culturally recognizable trope of the "rogue as trickster" and "rogue as critic" to contextualize his deceptive and illegal activities, before signaling his desire for rehabilitation by exiting banking and futures trading – thereby enacting the "rogue as family man". Practical implications: The application of a narratological methodology opens up new avenues for understanding the interplay between Western cultural institutions, entrepreneur selves, and autobiographical writing. Originality/value: This paper shows that narratology provides a new methodological window through which management historians can view entrepreneur autobiographies.